Diseño de una máquina de corte por plasma con control numérico computarizado para planchas de acero. - Llambo Toalombo, Jonathan Stalin (2021)
The objective of this project is to design a plasma cutting machine controlled by computerized numerical control to work with metal plates up to 12 mm thick, which is the maximum dimension with which small and medium-sized metalworking workshops in zone 3 of the city work. country. The methodology used in this work was based on a conceptual design stage where reference is made to the operating logic of the machine and the constitution of each of its parts; Through this, the initial variables to be considered were determined, which were later evaluated in the dimensional design stage based on their most important characteristics and by calculation methods applied to each selected system. In the next stage, the detailed design is contemplated through the use of CAD software where the different systems or components that make up the machine are represented and their design analysis is carried out. With this information, the electromechanical design is obtained for a machine that cuts steel plates with dimensions of 1220 x 1220 mm and thickness of up to 12 mm, the same that is justified through the use of CAE simulation software by the finite element method. , obtaining the following results: the machine can withstand stresses of 7,635 MPa, a maximum deformation of 2.691 mm in the central supports with a safety factor of 2.7, which is acceptable as it is higher than that recommended for the design of static structures which is between 1.25 and 2.